Principle Of Mathematical Induction

Question
CBSEENMA11014333

Deduce projection formula from sine formula

Solution

We have to show that
            straight a space equals space straight b space cosC space plus space straight c space cosB
  R.H.S.     = b cosC + c cosB = k sinB cos C + k sin C cos B
                = k [sin (B + C)] =  k sin(straight pi-A)                    [By sine formula]
                = k sinA = a = L.H.S.
               

Sponsor Area

Some More Questions From Principle of Mathematical Induction Chapter